Analisis Yuridis Prasyarat Mantan Narapidana Dalam Pemilu Legislatif Menurut Undang-Undang Pemilu - Wahyudin, M Yahya (SIYASI: Jurnal Trias Politica, 2023)
Elections as one of the procedures in a democratic country have gone through a long journey, especially when talking about elections in Indonesia. Indonesia as a democratic country and also a rule of law state also regulates election matters in statutory regulations, namely Law Number 7 of 2017 concerning General Elections, but Law Number 7 of 2017 concerning Elections does not always work in an ideal system, in the Law No. The law regulates ex-convicts to be able to run in legislative elections, ex-convicts are explicitly allowed to run in legislative elections with several conditions. If you look at one form of an ideal system, elections should be a forum for selecting candidates for leaders or representatives of the people who are clean and have integrity without any criminal records. However, Article 240 Paragraph 1 Letter g allows ex-convicts to run for election to the legislature, this article creates uproar and is often tested for constitutionality in the Constitutional Court through the Judicial Review review  Pemilu sebagai salah satu prosedur dalam negara demokrasi telah melalui perjalanan panjang terutama jika berbicara pemilu di Indonesia. Indonesia sebagai negara demokrasi dan juga negara hukum juga mengatur soal pemilu dalam peraturan perundang-undangan yaitu Undang-Undang Nomor 7 Tahun 2017 tentang Pemilihan Umum, namun Undang-Undang Nomor 7 Tahun 2017 tentang Pemilu tersebut tidak selalu berjalan pada sistem ideal, dalam Undang-Undang tersebut mengatur tentang mantan narapidana untuk bisa maju dalam pemilu legislatif, secara eksplisit mantan narapidana diperbolehkan untuk maju dalam pemilu legislatif dengan beberapa syarat. Jika melihat pada satu bentuk sistem ideal seharusnya pemilu menjadi wadah untuk memilih calon pemimpin atau waki rakyat yang bersih dan berintegritas tanpa ada catatan kriminal. Namun pada pasal 240 Ayat 1 Huruf g memperbolehkan mantan narapidana untuk bisa mencalonkan diri dalam pemilu legislatif, tenunya pasal tersebut melahirkan kegaduhan dan seringkali di uji konstitusionalitasnya di Mahkamah Konstitusi melalui jalur Judicial Review.